Performance Aspects of Retrodirective RFID Tags - Theodoros N. F. Kaifas (Engineering Proceedings, 2024)
Although RFID(radio frequency identification) tags do not require a direct line of sight, their operational range is often characterized as being limited. Indeed, in the case of passive RFID tags, the interrogating signal from the transmitter needs to reach the tag’s radio transponder and trigger a nearly omnidirectional scattered signal to be harvested by the receiver. This two-way (from Tx to the tag and back to Rx) channel exhibits increased attenuation not only due to the doubled distance (in case Tx and Rx are collocated) but also to the uncontrolled (i.e., unfocused) backscattering. In the work at hand, we propose a way to control the backscattered radiation and focus the produced beam towards the direction of the reader (the Tx-Rx device). Indeed, one can utilize the concept of retrodirective arrays to immediately control the direction of departure of the backscatter link, maximizing the scattered power towards the reader and thus delivering an increase in the operational range of the tag. This of course means that in this case, the tag should be equipped with a minimum of two element radiators. Thus, retrodirective RFID array tags are introduced in the current work to increase the operating range with minimal costs and levels of complexity since 90° hybrids are used to achieve proper backscattering. To evaluate the proposed passive tag array, performance aspects are addressed. Specifically, we examine the Bit Error Rate with respect to the Signal to Noise Ratio for the retrodirective tag, the one antenna, the broadside, and the spatial diversity array. The results prove that the proposed tag allows for a significant increase in the operational range.